Exosome-based strategy for degenerative disease in orthopedics: Recent progress and perspectives - Rongjie Wu; Haotao Li; Chuanwei Sun; Jialin Liu; Duanyong Chen; Haiyang Yu; Zena Huang; Sien Lin; Yuanfeng Chen; Qiujian Zheng (Journal of Orthopaedic Translation, 2022)
Background: Degenerative diseases in orthopaedics have become a significant global public health issue with the aging of the population worldwide. The traditional medical interventions, including physical therapy, pharmacological therapy and even surgery, hardly work to modify degenerative progression. Stem cell–based therapy is widely accepted to treat degenerative orthopaedic disease effectively but possesses several limitations, such as the need for strict monitoring of production and storage and the potential risks of tumorigenicity and immune rejection in clinical translation. Furthermore, the ethical issues surrounding the acquisition of embryonic stem cells are also broadly concerned. Exosome-based therapy has rapidly grown in popularity in recent years and is regarded as an ideal alternative to stem cell–based therapy, offering a promise to achieve ‘cell-free’ tissue regeneration. Methods: Traditionally, the native exosomes extracted from stem cells are directly injected into the injured site to promote tissue regeneration. Recently, several modified exosome–based strategies were developed to overcome the limitations of native exosomes, which include mainly exogenous molecule loading and exosome delivery through scaffolds. In this paper, a systematic review of the exosome-based strategy for degenerative disease in orthopaedics is presented. Results: Treatment strategies based on the native exosomes are effective but with several disadvantages such as rapid diffusion and insufficient and fluctuating functional contents. The modified exosome–based strategies can better match the requirements of the regeneration in some complex healing processes. Conclusion: Exosome-based strategies hold promise to manage degenerative disease in orthopaedics prior to patients reaching the advanced stage of disease in the future. The timely summary and highlights offered herein could provide a research perspective to promote the development of exosome-based therapy, facilitating the clinical translation of exosomes in orthopaedics. Translational potential of this article: Exosome-based therapy is superior in anti-senescence and anti-inflammatory effects and possesses lower risks of tumorigenicity and immune rejection relative to stem cell–based therapy. Exosome-based therapy is regarded as an ideal alternative to stem cell–based therapy, offering a promise to achieve ‘cell-free’ tissue regeneration.